CHILDREN IN SINGLE MOTHER FAMILIES: OUTCOMES OF SOCIAL CONSTRUCTION AND POLICY DESIGN OF SINGLE MOTHER FAMILIES - Skubiejute, Greta (PEOPLE: International Journal of Social Sciences, 2019)
The main issue analysed in the paper is policy design and its outcome on social construction of single mother families as well as on the wellbeing of single mother’s children. Literature review and qualitative legislation documents analysis has been conducted to demonstrate how single mothers are perceived in different welfare state regimes and the case of Lithuania is presented. The main findings of the paper show that in the welfare regimes (such as social democratic) where single mother families are seen as equal families to traditional family, policy strikes to provide the children with equal opportunities despite family circumstances, while other regimes (such as post-soviet) concentrate on controlling demography and therefore promote traditional families and children from single mother families are rather neglected. Moreover, all the welfare regimes and their policies fail to recognise the diversity within single mother families and therefore, at the end, children are not set equally.